PENATAAN ORGANISASI PERANGKAT DAERAH BERDASARKAN PERATURAN PEMERINTAH NOMOR 18 TAHUN 2016 DI KOTA PALANGKA RAYA - Novi Yuliantie; Nuhing (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2018)
This research is to describe a process that occurs in structuring the regional government. In the environment of the City Government of Palangka Raya which currently applies government regulation Number 18/2016 concerning regional devices as well as supporting factors and inhibitors. Indicators in organizational arrangement have two roles, efficiency and effectiveness. In this study the authors used qualitative research methods with emphasis to the Regional Secretariat of the City of Palangka Raya where the existence of the Organization Section was discussed. The technique of collecting data uses observation, interviews, and documentation. Based on the results of the study (1) Structuring Regional organizations based on government regulation Number18/2016 is still not going well, this is analyzed from indicators of the regional organizational arrangement process, namely Environment, Strategy and Technology as government implementation so that public services can be implemented regions, which are determined by the decision of the Mayor of Palangka Raya in order to realize a regional apparatus institution in accordance with government regulation Number 18/2016. (2) Supporting factors: Facilities and Infrastructure and inhibiting factors: HR and number of employees (3) Suggestion: must always evaluating and reviewing its institutions, not increasing the number of civil servants who are not functional and contract workers, and to better utilize the potential of the organizational section as apparatus resources need to be placed. Keywords: Organizational Arrangement, Government Regulations, Mayor Regulations